The role of the gastroenterologist in non-IgE mediated gastrointestinal food allergy. Issue 10 (October 2016) - Foong, Ru-Xin; Brough, Helen A.; Lozinsky, Adriana Chebar; Shah, Neil
Abstract: The prevalence of food allergy has been on the rise in the UK over the last 30 years. Food allergy can be classified as Immunoglobulin E (IgE)-mediated, non-IgE mediated or mixed IgE and non-IgE mediated food allergy. Whilst the management of IgE-mediated food allergy is relatively well established with regards to investigations and treatment options, non-IgE mediated food allergy management is emerging. The role of the gastroenterologist in food allergy is in the management of non-IgE mediated gastrointestinal food allergy, which is performed closely alongside allergologists. The aim of this review is to discuss the common presentations of non-IgE mediated food allergy (i.e. cow's milk protein allergy, food protein-induced enterocolitis, eosinophilic gastrointestinal disorders) and describe current investigation and treatment options for these conditions. It focuses on the main management options available such as elimination diets, drug therapies, as well as gastroenterology-specific tests such as endoscopy. It also highlights the importance of both allergy and gastroenterology multi-disciplinary team support in order to ensure the best management of these children.